Alineamiento de la producción científica a las prioridades de investigación en el Seguro Social de Salud del Perú: Propuesta de fortalecimiento y descentralización de la investigación: Propuesta de fortalecimiento y descentralización de la investigación - Alarcon-Ruiz, Christoper A. (2022)
Background: One of the impact indicators of priorities in health research-setting is the scientific production that refers to these priorities. EsSalud raised nine priority research topics (PRT) and 20 priority research questions (PRQ) for the 2017-2019 period. We assess the alignment to these research priorities in the scientific articles published during the 2017-2020 period by EsSalud, and we characterize those financed by this institution. Material and Methods: Analysis of the scientific articles registered in the EsSalud scientific production database for the period 2017-2020. We used a standardized methodology and in duplicate to evaluate the alignment of a scientific article to the PRT and PRQ 2017-2019 of EsSalud. The evaluation of the alignment to the PRQs is only carried out in original articles and congress summaries. We report alignment frequencies to each PRT and PRQ, and we report the frequency of alignment to at least one PRT according to the articles' characteristics. In addition, the characteristics of the articles financed by EsSalud were reported. Results: 170 out of 1283 articles were aligned to at least one PRT. Eight of the twenty PRQs went unanswered. Articles with authors who belong to or received funding from IETSI-EsSalud had the highest alignment rate. Finally, the highly cited articles financed by EsSalud were mainly observational studies, clinical practice guidelines and systematic reviews. Conclusion: The articles published by EsSalud during 2017 to 2020 have low alignment with institutional research priorities. Furthermore, it is necessary a process of implementation, monitoring, and evaluation of research priorities in the institution.